Women in business: Using local chicken breeds to empower African families - International Livestock Research Institute (International Livestock Research Institute, 2021)
This video shows the rationale behind the ‘Women in business: chicken seed dissemination in Ethiopia and Tanzania’ project and its main approach to supporting women’s empowerment through the dissemination of improved chicken breeds.